Using Compulsory Licenses to Facilitate Access to Medicines: The Indian Experience - Ristanic,Aleksandar (2016)
The attempts to make use of a compulsory licensing provision under the TRIPS Agreement brought human rights, notably, the right to health, into the foreground of the debate between patents and access to medicines. This whole thesis is about the existing tensions between the two regimes – patents and human rights. The growing scholarship that has been devoted to these tensions can be divided into two groups – those who believe that intellectual property and human rights are in a conflict and those who take the view that they are compatible and can coexist. This thesis takes the perspective of coexistence based on the premise that innovation and access, as major interests in the debate, are familiar to both patents and human rights. The thesis accordingly seeks to adopt a dialectic approach that tries to reconcile these two sides by critically scrutinizing the recent developments in relation to compulsory licensing. The thesis uses the Indian case of Bayer v. Natco as a vehicle to discuss the core issues arising from the debate between patents and human rights.
Keywords: compulsory license; patent; pharmaceutical patent; access to medicines; human right to health; human right to science and culture; right to property; the TRIPS Agreement; the TRIPS flexibilities; India; the Bayer/Natco case